Topical Corticosteroid Abuse on the Face: A Prospective Study of Garments Workers Appearing at Dermatology Outpatients in a Private Medical College Hospital (Medicine Today, 2015)
Abuse of topical corticosteroids (TC), especially over the face, is common not only in Bangladesh but also prevalent worldwide. Data about the magnitude of this problem in our country is lacking. The aims of this study were to find out the demographics, magnitude and clinical features of TC misuse on the face in the dermatology outpatient department (OPD) as well as to raise awareness about this problem and to analyze its causes. This was a prospective questionnaire-based clinical study conducted among the garments workers who visited the out patient department of a non government medical college hospital. Garments workers with relevant facial dermatoses reporting to the investigator were asked about their current use of over-the-counter topical formulations and a structured questionnaire applied in case the same was confirmed to be TC. A total of 895 garments workers with facial dermatoses were screened, of which 129 (14.41%) were using TC. TCs were used for treating acne in 53 (41.0%), as a lightening agent in melasma in 34 (26.4%), general face cream/fairness cream/after shave cream in 21 (16.3%). Steroid combinations were used by 84 (65.12%). Most of the patients (n =90; 70%) belonged to rural areas, followed by those hailing from suburban areas (n = 31; 24%).15 out of 22 (68%) prescriptions by doctors were for products in the milder steroid group, whereas 98 of 107 (91.6%) recommendations by non-physicians were for potent steroids (P< 0.001). 118 of the 129 patients (91.5%) have shown adverse effects. Acne/exacerbation of acne was the most common adverse effect. TC misuse in garments workers with facial dermatoses is quite common, and most of this use is unwarranted. Use as a treatment for acne is the most common indication in this cohort.Medicine Today 2015 Vol.27(1): 23-26